2011
DOI: 10.1371/journal.pone.0020151
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Electron Transport Chain Complexes in Capsaicin Mediated Oxidative Stress Leading to Apoptosis in Pancreatic Cancer Cells

Abstract: We evaluated the mechanism of capsaicin-mediated ROS generation in pancreatic cancer cells. The generation of ROS was about 4–6 fold more as compared to control and as early as 1 h after capsaicin treatment in BxPC-3 and AsPC-1 cells but not in normal HPDE-6 cells. The generation of ROS was inhibited by catalase and EUK-134. To delineate the mechanism of ROS generation, enzymatic activities of mitochondrial complex-I and complex-III were determined in the pure mitochondria. Our results shows that capsaicin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 46 publications
7
146
0
Order By: Relevance
“…No mutagenic activity was observed in any of the five bacterial strains, in any of the activation conditions. Essentially identical results were reported by Proudlock et al (2004). Tsuchiya et al (2011) demonstrated mutagenicity of chili pepper extract in strain TA98, while pure capsaicin was inactive in the same assay; subsequent analysis of the chili pepper samples identified the presence of carcinogenic aflatoxins B1 and G1.…”
Section: In Vitro Genotoxicitysupporting
confidence: 83%
See 1 more Smart Citation
“…No mutagenic activity was observed in any of the five bacterial strains, in any of the activation conditions. Essentially identical results were reported by Proudlock et al (2004). Tsuchiya et al (2011) demonstrated mutagenicity of chili pepper extract in strain TA98, while pure capsaicin was inactive in the same assay; subsequent analysis of the chili pepper samples identified the presence of carcinogenic aflatoxins B1 and G1.…”
Section: In Vitro Genotoxicitysupporting
confidence: 83%
“…Arceo et al (1995) also showed a significant increase in number of peripheral blood cells with micronuclei. The micronucleus assay was repeated by groups with >98% pure capsaicin, both times yielding negative results: Chanda et al (2004) administered capsaicin orally to male mice at dose levels up to 800 mg/kg and females received 200 mg/kg; Proudlock et al (2004) administered capsaicin subcutaneously using an escalating dosing regime up to 500 mg/kg. Earlier, Villaseñor et al (1993) had also shown that capsaicin at a maximum tolerable dose of 1.22 mg/kg (intraperitoneally) was not mutagenic in the same assay.…”
Section: In Vivo Genotoxicitymentioning
confidence: 99%
“…To examine how sensory neurons impact PDAC initiation and progression, we first determined if neonatal capsaicin had direct effects on pancreatic cells because previous studies using cancer-derived cell lines showed it affected apoptosis and proliferation (28)(29)(30)(31)(32)(33)(34). The neurotoxic effects of neonatal capsaicin treatment are assumed to be via binding to TRPV1, the vanilloid receptor specific for capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to GSH, catalase and SOD play important role to detoxify hydrogen peroxide and super-oxides, respectively. A number of therapeutic agents have been shown to increase intracellular ROS generation by downregulating antioxidant enzymes such as catalase and SOD (7,20,23). However, some other studies have reported that reduction in intracellular GSH is necessary for the formation of ROS (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiolipin oxidation was determined by staining the cells with 10-N-nonyl acridine orange (NAO), a probe specific for mitochondrial membrane cardiolipin (20). Briefly, U87 cells were incubated with 40 lM alantolactone for 0, 6, and 12 h. After treatment, cells were further incubated with DCFH-DA (10 lM), Rhodamine 123 (5 lg/ml), and NAO (5 lM) in the dark for 30 min.…”
Section: Apoptosis Assaymentioning
confidence: 99%